Pericyte-mediated regulation of angiogenesis during cutaneous wound healing in adult zebrafish - Tomohiro Ishii; Shinya Yuge; Koji Ando; Weibin Zhou; Shigetomo Fukuhara (Communications Biology)
Abstract Pericytes are mural cells that wrap small caliber vessels, playing a crucial role in stabilizing vascular structure. Upon induction of angiogenesis, pericytes were thought to detach from the vessel wall, thereby facilitating the sprouting of endothelial cells (ECs). However, the precise roles of pericytes in regulating angiogenesis still remain elusive. Here, we demonstrate, by performing live-imaging of adult zebrafish, that pericytes actively regulate angiogenesis during wound healing. We generated a zebrafish line which enables the conditional ablation of mural cells, including pericytes, and analyzed cutaneous wound angiogenesis. Loss of pericytes significantly increased the number of sprouting events of ECs and promoted their proliferation, resulting in the formation of dense and disorganized blood vessel networks. Furthermore, in the absence of pericytes, the injured vessels showed abnormal vessel elongation, thereby generating ectopic vascular networks. These results suggest that pericytes play an active role for generating functional blood vessels during wound angiogenesis.